Flexible and Stretchable 3ω Sensors for Thermal Characterization of Human Skin. (15th May 2017) - Tian, Limei; Li, Yuhang; Webb, Richard Chad; Krishnan, Siddharth; Bian, Zuguang; Song, Jizhou; Ning, Xin; Crawford, Kaitlyn; Kurniawan, Jonas; Bonifas, Andrew; Ma, Jun; Liu, Yuhao; et al.
Abstract : Characterization of the thermal properties of the surface and subsurface structures of the skin can reveal the degree of hydration, the rate of blood flow in near‐surface micro‐ and macrovasculature, and other important physiological information of relevance to dermatological and overall health status. Here, a soft, stretchable thermal sensor, based on the so‐called three omega (i.e., 3ω) method, is introduced for accurate characterization of the thermal conductivity and diffusivity of materials systems, such as the skin, which can be challenging to measure using established techniques. Experiments on skin at different body locations and under different physical states demonstrate the possibilities. Systematic studies establish the underlying principles of operation in these unusual systems, thereby allowing rational design and use, through combined investigations based on analytical modeling, experimental measurements, and finite element analysis. The findings create broad opportunities for 3ω methods in biology, with utility ranging from the integration with surgical tools or implantable devices to noninvasive uses in clinical diagnostics and therapeutics. Abstract : A soft, stretchable thermal sensor based on the three omega (i.e., 3ω) method enables accurate characterization of the thermal properties of diverse materials systems such as the human skin. Rational design of these sensors creates broad opportunities for 3ω methods in biology, with utility ranging from integration with surgical tools or implantable devices to noninvasive uses in clinical diagnostics and therapeutics.